Macrophage cytotherapy on liver cirrhosis - Ping, Dabing; Peng, Yuan; Hu, Xudong; Liu, Chenghai (Frontiers in Pharmacology, 2023)
Macrophages, an essential cell population involved in mediating innate immunity in the host, play a crucial role on the development of hepatic cirrhosis. Extensive studies have highlighted the potential therapeutic benefits of macrophage therapy in treating hepatic cirrhosis. This review aims to provide a comprehensive overview of the various effects and underlying mechanisms associated with macrophage therapy in the context of hepatic cirrhosis.